EXAMINING POSITIVE AFFECT IN THE ASSOCIATION OF SLEEP DISTURBANCE AND ABILITY TO PARTICIPATE IN SOCIAL ACTIVITIES. (11th November 2018) - Tighe, C; Dautovich, N; Allen, R
Abstract: Sleep disturbance is associated with limitations in social functioning. Positive affect plays a buffering role in the context of stress and psychosocial outcomes and may also serve this role in relation to sleep disturbance. Study objectives were to determine: 1) the moderating role of positive affect in the association of sleep disturbance and perceived ability to participate in social activities, and 2) whether this association is moderated by age. Study materials were completed online by 216 adults (20–80 years-old; M=44.9 years±15.6) at a single time-point. Sleep disturbance was measured using the PROMIS® 8-item Sleep Disturbance-Short Form, positive affect with the Positive and Negative Affect Schedule, and ability to engage in social activities with the PROMIS® 4-item Ability to Participate in Social Roles and Activities-Short Form. PROCESS regression-based moderation analyses were used to test the study objectives. Adjusting for covariates, positive affect significantly moderated the negative association of sleep disturbance and social activity participation (Coefficient=.04, p=.02); at higher levels of sleep disturbance, social activity participation was less limited when positive affect was high. The sleep disturbance, positive affect, and age interaction was nonsignificant (p=.10). Individuals who had high levels of positive affect despite experiencing higher levels of sleep disturbance felt better able to engage socially. Though this association was not significantly moderated by age, a trend suggested that at younger ages and lower levels of sleep disturbance, higher levels of positive affect were associated with poorer social functioning. Future work should further explore socioemotional selectivity in the context of sleep.